MULTILITERACY: ALTERNATIVE LEARNING MODELS TO IMPROVE ECOLOGICAL LITERACY OF PRIMARY SCHOOL STUDENTS - Dede Margo Irianto , Hana Yunansah , Tita Mulyati , Yusuf Tri Herlambang , Dadan Setiawan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study investigates the effects of multiliteracy learning models on the ecological literacy abilities of elementary school students and discovers how students describe their experiences in learning. This study uses an explanatory sequential design that is part of the mixed method. The use of explanatory sequential design allows the collection of quantitative and qualitative data that serve as corroborating evidence to answer two research questions: how are students’ ecological literacy skills between students who learn to use multiliteracy learning models and students who learn to use traditional models ? How can the experience gained by students learning with multiliteracy models be useful to improve their ecological literacy skills? Quantitative results demonstrate that the use of the learning model multiliteracy significant effect on the improvement of ecological literacy skills of elementary school students. Then the qualitative findings of this elucidation are students are of the view that the learning experience experienced can strengthen and enhance their knowledge making it easier for them to solve problems encountered, students find it easy to find information because learning allows them to access information from various sources both print and media electronics, and learning experiences using multiliteracy models help students realize that humans must take good care of nature/ the environment.